The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2020
DOI: 10.1371/journal.pone.0239514
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of bioclimatic change in Kazakhstan, end 20th—middle 21st centuries, according to the PRECIS prediction

Abstract: We evaluate bioclimatic changes in Kazakhstan from the end of the 20th century until the middle of the 21st century to offer natural resource managers a tool that facilitates their decision-making on measures to adapt agriculture and environmental care to foreseeable climate change. We use climatic data from the “Providing REgional Climates for Impact Studies” (PRECIS) prediction and study them following the Worldwide Bioclimatic Classification System (WBCS) of Rivas-Martínez. For three 25-year intervals (1980… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 40 publications
0
1
0
Order By: Relevance
“…A study of the bioclimate in Kazakhstan showed that over the past 50 years there has been -an increase in warmth in 36.2% of the area, an increase in continentality in 7.3% of the area, and an increase in annual aridity in 10.3% of the area. In the mountains there is a risk of disappea-rance of all three mountain bioclimates (Lopez Fernandez et al, 2020). Plants make up the majority of terrestrial biomass worldwide.…”
Section: Discussionmentioning
confidence: 99%
“…A study of the bioclimate in Kazakhstan showed that over the past 50 years there has been -an increase in warmth in 36.2% of the area, an increase in continentality in 7.3% of the area, and an increase in annual aridity in 10.3% of the area. In the mountains there is a risk of disappea-rance of all three mountain bioclimates (Lopez Fernandez et al, 2020). Plants make up the majority of terrestrial biomass worldwide.…”
Section: Discussionmentioning
confidence: 99%
“…The agricultural sector occupies most of Kazakhstan, about 2 million km 2 , which makes up 77% of the sector's area and employs 25% of its labor resources (Fernandez et al, 2020). However, the majority of cultivated lands sit in Northern Kazakhstan.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, a lot of studies have been published that analyzed various aspects of the impact of climate change on various sectors in Kazakhstan, in particular on water resources, mudflows, glaciers, snow cover, dust storms, and the agricultural sector, which show that the recurrence of these phenomena has increased over the past decade [10][11][12][13][14][15][16][17][18][19][20][21][22][23]. Such publication activity indicates that the study of extreme natural events is a rather urgent task for Kazakhstan, the solution of which is a key factor in the process of creating an early warning system, adapting, and the reduction in vulnerability.…”
Section: Introductionmentioning
confidence: 99%